Association of insurance disparities and survival in adults with multiple myeloma: A non-concurrent cohort study. (May 2021) - Makhani, Sarah S.; Shively, Dana; Castro, Grettel; Rodriguez de la Vega, Pura; Barengo, Noël C.
Highlights: Multiple myeloma (MM) accounts for 10 % of all hematological malignancies​. The literature has identified socioeconomic barriers in receiving advanced treatments. Uninsured patients had a 26 % increased hazard of mortality vs. private insurance. Five-year hazard of mortality was significantly higher in those with Medicaid. Abstract: Background: Multiple myeloma (MM) accounts for 10 % of all hematological malignancies. As recent advances in MM treatment continue to improve survival rates, socioeconomic barriers need to be identified to ensure equal treatment. This study evaluates the association between insurance status and survival in patients with MM. Methods: This study analyzed patients with MM from the 2007–2016 Surveillance, Epidemiology, and End Results (SEER) Program database. Insurance status was categorized as uninsured, Medicaid, private insurance, and other insurance. Cancer-specific survival was measured at one- and five-years post diagnosis. Results: From 2007–2016, there were 41, 846 patients with MM extracted from the SEER database. Those with private insurance had a higher proportion of participants that identified as married (65.5 %), resided in metropolitan cities (90.1 %), and identified as white (76 %) and non-Hispanic (90.8 %). The uninsured group had the highest proportion of Black participants compared to other insurance groups (37.4 %). After adjustment for age, sex, race, ethnicity, marital status, and residence, the likelihood of five-year survival was significantly lower in those respondents with Medicaid (adjusted (adj) Hazard Ratio (HR): 1.44; 95 % Confidence Interval (CI): 1.36−1.53), when compared with private insurance holders. Those who were uninsured had a 26 % increased mortality hazard than those with private insurance (95 % CI 1.04−1.53). Conclusion: After adjustment, insurance status can influence the survival of adults with MM. As treatment modalities for MM continue to advance, the insurance status of a patient should not hinder their ability to receive the most effective and timely therapies.